Assessing Validity of Some Critiques towards the Fatwas of the DSN - MUI on Mudarabah within the Perspective of the Aqwal of Islamic Legal Expert - Kamaluddin, Safrudin Halimy; Sudarman, Sudarman (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2020)
Abdullah Saeed and Mervyn K. Lewis argue that the implementation of contracts in Islamic banking has deviated from fiqh. With the same critical framework, some researchers in Indonesia also criticize the fatwas of the DSN-MUI (National Sharia Board of the Indonesian Ulema Council) on the muá¸Ärabah contract. This paper, however, argues that all of those criticisms can be categorized as a khilÄfiyyah (differences of opinion among muslim jurists). Again this backdrop, this paper will assess the validity of those critiques towards the fatwas of the DSN-MUI on muá¸Ärabah within the perspective of the aqwÄl of islamic legal experts (madhÄhib) as well as prove that the muá¸Ärabah model in Islamic banking in Indonesia does not deviate from fiqh. After reviewing relevant library sources, this paper shows that the fatwas of the DSN-MUI on muá¸Ärabah are supported by the aqwÄl of islamic legal experts among á¸¤anbalÄ«, á¸¤anafÄ«, MÄlikÄ«, and ShÄfiÊ»Ä« schools. Moreever, although it is different from the muá¸Ärabah form known by many people in fiqh, the muá¸Ärabah contract system adopted by the DSN-MUI can be categorized as a model of muá¸Ärabah permitted by islamic legal experts.